STUDI PENDAHULUAN E-LKPD BERBASIS DISCOVERY LEARNING MATERI FILTRASI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF - Sriyanti, Ida; Jannah, Fathya Nurul; Siahaan, Sardianto Markos (EduFisika: Jurnal Pendidikan Fisika, 2025)
Developing students’ creative thinking skills remains a challenge in science learning, particularly when instructional materials do not adequately support exploration and contextual understanding. This study aims to develop an e-LKPD product based on discovery learning and nanofiber membrane filtration to train junior high school students' creative thinking skills effectively. The study employed a development research approach using the ADDIE model and involved 217 seventh-grade students from 10 classes (VIIA-VIIJ) at SMPN 1 Jambi. The data collection technique in this study was to distribute questionnaires, which were then analyzed using the Content Validity Ratio (CVR) to determine feasibility, one-to-one and small-group evaluations to assess practicality, and N-gain analysis to measure effectiveness. The results showed that all aspects of the e-LKPD met the feasibility criteria and were categorized as very good, with minor revisions related to writing clarity. The practicality analysis indicated a high level of usability, with average scores of 86.76% in the one-to-one evaluation and 95.53% in the small group evaluation. The N-gain analysis yielded an average score of 0.46, which falls into the moderate effectiveness category, indicating an improvement in students’ creative thinking skills. It can be concluded that the development of e-LKPD based on discovery learning for nanofiber membrane-assisted filtration materials is feasible, practical, and moderately effective, and has the potential to serve as an alternative digital learning resource to support the development of creative thinking in junior high school science learning.